Blockade of monoacylglycerol lipase inhibits oligodendrocyte excitotoxicity and prevents demyelination in vivo. Issue 1 (8th August 2014) - Bernal‐Chico, Ana; Canedo, Manuel; Manterola, Andrea; Victoria Sánchez‐Gómez, María; Pérez‐Samartín, Alberto; Rodríguez‐Puertas, Rafael; Matute, Carlos; Mato, Susana
<x xml:space="preserve">Abstract</x> The endocannabinoids 2‐araquidonoylglycerol (2‐AG) and anandamide (AEA) are bioactive lipids crucially involved in the regulation of brain function in basal and pathological conditions. Blockade of endocannabinoid metabolism has emerged as a promising therapeutic strategy for inflammatory diseases of the central nervous system, including myelin disorders such as multiple sclerosis. Nevertheless, the biological actions of endocannabinoid degradation inhibitors in oligodendrocytes and white matter tracts are still ill defined. Here we show that the selective monoacylglycerol lipase (MAGL) inhibitor JZL184 suppressed cell death by mild activation of AMPA receptors in oligodendrocytes in vitro, an effect that was mimicked by MAGL substrate 2‐AG and by the second major endocannabinoid AEA, in a concentration‐dependent manner, whereas inhibition of the AEA metabolizing enzyme fatty acid amide hydrolase with URB597 was devoid of effect. Pharmacological experiments suggested that oligodendrocyte protection from excitotoxicity resulting from MAGL blockade involved the activation of cannabinoid CB1 receptors and the reduction of AMPA‐induced cytosolic calcium overload, mitochondrial membrane depolarization, and production of reactive oxygen species. Administration of JZL184 under a therapeutic regimen decreased clinical severity, prevented demyelination, and reduced inflammation in chronic experimental autoimmune encephalomyelitis. Furthermore, MAGL inactivation robustly preserved myelin integrity and suppressed microglial activation in the cuprizone‐induced model of T‐cell‐independent demyelination. These findings suggest that MAGL blockade may be a useful strategy for the treatment of immune‐dependent and ‐independent damage to the white matter. GLIA 2015;63:163–176